Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Olahan Jagung Hibrida dalam Meningkatkan Nilai Tambah Ekonomi di Desa Karangkajen - Putri, Salmayunicha Listie; Yunianingsih, Rika; Syahbani, Dwi Gustavina; Cahyani, Maulidha Putri; Purnomo, Josephine Oktavidhani; Nugroho, Albar Kresna Lukito; Wibowo, Amanda Aulia; Sinuraya, Suci Iriani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The potential of hybrid corn in Karangkajen Village, Magelang Regency, has not been optimally utilized because the harvest is only sold raw as animal feed with low economic value. This community empowerment aims to empower PKK mothers and women farmers through product diversification to create added value and business opportunities. The method used was Participatory Action Research with participatory training techniques, involving 34 participants in the practice of making cornstarch and paper glue from hybrid corn. As a result, the participants successfully produced both products, understood production cost analysis, and simple packaging and marketing strategies. This activity received an enthusiastic and participatory response from the community. It was concluded that assistance in processing agricultural products has the potential to increase income and encourage economic independence based on local potential, so it needs to be supported by sustainability strategies.